2018
DOI: 10.3390/en11010256
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Bubble Coalescence and Breakup in the Reactor Fuel Channel with a Vaned Grid

Abstract: The characteristics of bubbles of different sizes in fuel assembly are vital to two-phase flow resistance and heat transfer capacity. However, due to the swirl flow caused by the mixing vane, bubbles can crowd at the heated surface, which may anticipate the occurrence of departure from nucleation boiling. In the current work, the adiabatic two-phase flow in a simplified fuel assembly was analyzed by using the Eulerian two-fluid model and the MUSIG (MUltiple SIze Group) model. This computational domain consists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The coefficient C L changes its sign at a bubble diameter of d = 5.8 mm for our conditions. It was previously shown that this expression of the lift force can be sufficiently used for predictions of bubbly flows in complex geometrical conditions, as example in fuel columns with grid spacers [34]. C TD = 0.1 is the coefficient of turbulent diffusion [23].…”
Section: Interface Forcesmentioning
confidence: 99%
“…The coefficient C L changes its sign at a bubble diameter of d = 5.8 mm for our conditions. It was previously shown that this expression of the lift force can be sufficiently used for predictions of bubbly flows in complex geometrical conditions, as example in fuel columns with grid spacers [34]. C TD = 0.1 is the coefficient of turbulent diffusion [23].…”
Section: Interface Forcesmentioning
confidence: 99%
“…The number of investigations into the flow and mixing mechanisms is limited, probably due to difficulties encountered in obtaining meaningful experimental measurements. Bubble coalescence and breakup are the main phenomena for gas-liquid fluid flow inside the devices [25]. Recently, Falzone et al [26] concluded four main mechanisms leading to bubble breakup, which were turbulent fluctuation, macroscopic shear stress, turbulent shear stress and interfacial slip.…”
Section: Introductionmentioning
confidence: 99%